Simple prediction model for homologous recombination deficiency in breast cancers in adolescents and young adults - Watanabe, Tomoko; Honda, Takayuki; Totsuka, Hirohiko; Yoshida, Masayuki; Tanioka, Maki; Shiraishi, Kouya; Shimada, Yoko; Arai, Eri; Ushiama, Mineko; Tamura, Kenji; Yoshida, Teruhiko; Kanai, Yae; et al. (Breast cancer research and treatment, 2020)
Purpose Homologous recombination deficiency (HRD), which influences the efficacy of PARP inhibitor- and platinum agent-based therapies, is a prevalent phenotype of breast cancer in adolescents and young adults (AYAs; 15–39 years old). However, HRD score, indicating HRD status, is not routinely assessed in the breast oncology clinic, particularly in patients without germline BRCA1/2 mutations. Hence, we sought to develop a model for determining HRD status based on genetic and clinicopathological factors. Methods Subjects were our own cohort of 46 Japanese AYA breast cancer patients and two existing breast cancer cohorts of US and European patients. Models for prediction of the HRD-high phenotype, defined as HRD score ≥ 42, were constructed by logistic regression analysis, using as explanatory variables genetic and clinicopathological factors assessable in the clinical setting. Results In all three cohorts, the HRD-high phenotype was associated with germline BRCA1/2 mutation, somatic TP53 mutation, triple-negative subtype, and higher tumor grade. A model based on these four factors, developed using the US cohort, was validated in the Japanese and European AYA cases: area under the receiver operating characteristic curve [AUC] was 0.90 and 0.96, respectively. A model based on three factors excluding germline BRCA1/2 mutation also yielded high-predictive power in cases from these two cohorts without germline BRCA1/2 mutations: AUC was 0.92 and 0.90, respectively. Conclusions The HRD-high phenotype of AYA breast cancer patients can be deduced from genomic and pathological factors that are routinely examined in the oncology clinic, irrespective of germline BRCA1/2 mutations.